2017
DOI: 10.29356/jmcs.v57i3.210
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Gold(I)-Chloroquine Complexes

Abstract: Two new gold(I) -chloroquine complexes, Au(CQ)(Cl) (<strong>1</strong>) and Au(CQ)(tgta) (<strong>2</strong>), were prepared and their most probable structure were established through a combination of different spectroscopic and analytical techniques. Their interaction with two important targets of action, DNA and thioredoxin reductase (TrxR), were nvestigated. These studies showed that complexes <strong>1</strong> and <strong>2</strong> displayed two types of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…Only the complexes 2, 5 and 7 show cytostatic effects at doses appreciably lower in comparison with cisplatin, chloroquine and doxorubicin under the same conditions. Interestingly, the complex 7 was the most active, with an of CQ enhances the biological activity of the metal complexes, as reported previously[6,8]. Under an inverted microscope, cell shape and changes in it can be observed clearly.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Only the complexes 2, 5 and 7 show cytostatic effects at doses appreciably lower in comparison with cisplatin, chloroquine and doxorubicin under the same conditions. Interestingly, the complex 7 was the most active, with an of CQ enhances the biological activity of the metal complexes, as reported previously[6,8]. Under an inverted microscope, cell shape and changes in it can be observed clearly.…”
supporting
confidence: 62%
“…ACCEPTED MANUSCRIPT 8 [RuCl(η 6 -C 10 H 14 )(4,4'-t-dibuthyl-2,2'-bipyridine)]PF 6 (5). Orange solid, yield 340 mg (78%).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These metal chelators, especially copper chelates, possess enhanced biological activity compared to the non-chelating drugs. Mechanistic studies have revealed that the difference is at least partially related to the redox features of the copper complexes [5,8,9]. However, information related to the effect of the interactions of metal chelating agents with biological molecules, such as human serum albumin (HSA) or bovine serum albumin (BSA) and DNA and their contribution to cytotoxicity has received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs used in the clinic have potent chelating ability, such as doxorubicin, ciprofloxacin, mercaptopurine and chloroquine, and have been shown to form metal complexes in vitro or in vivo (7)(8)(9). In vitro studies have demonstrated that the formed metal complexes exhibit enhanced (synergism) antitumor activity (10), indicating that their cytotoxicity at least partially is related to their metal chelating ability.…”
Section: Introductionmentioning
confidence: 99%